Disposal slope design based on low-plasticity rock’s shear strength in coal mining activities - Harjuni Hasan; Revia Oktaviani; Tommy Trides; Dionisyus Fransiskus Sinaga (Brawijaya University, 2022)
Slope stability is the primary factor in designing a stable slope. The strength of the disposal slope relies on the characteristic of the dump materials. The rock shear strength denotes rock ability to withstand the burden, both constant and dynamic load. The weakest material used as a reference in designing the disposal slope is siltstone in Pulaubalang formation (location-04). The safety value in Location 04 and 02 tend to drop quickly as the inclination increase, while the safety in location 01 and 03 tend to fall slowly. This indicates that rocks with a lower plasticity index tend to be stronger in steeper slope conditions. The slope geometry was designed to be 10, 15, 20, and 25 meters high with a slope angle of 10o, 15o, 20o, 25o, 30o, 35o, 40o, 45o, 50o, 55o, and 60o. The slope geometry is considered stable and safe. However, this study suggests that the most effective slope design is the slope with 25 meters high, overall slope of 25,3o; the single slope of 35o; berm width 4,66 meters, bench height of 5 meters, with the safety factor value of 4.30 (SF= 4.30).